An investigation on the influence of yogic methods on heart rate variability. Issue 1 (22nd August 2018) - Senthilnathan, Sengottuvel; Patel, Rajesh; Narayanan, Mariyappa; Katholil, Gireesan; Janawadkar, Madhukar Pandurang Rao; Radhakrishnan, Thimmakudy Sambasiva; Sharma, Krishna K.
Abstract: Background: The role of underlying mechanisms of yogic strategies which exert beneficiary effects on cardiac autonomic control is poorly understood. We have performed heart rate variability (HRV) analysis on subjects performing yogic methods and control subjects who mimic them through paced breathing and focused attention tasks using external cues. Methods: Heart rate (HR) time series is generated from electrocardiogram measured from subjects of yogic group (YG); performing yogic practices ( n = 15), paced breathing group (PBG); involved in breathing exercises cued at breathing rates (BR) from 3 to 15 cycles per minute (cpm) ( n = 23), normal breathing group (NBG) under regular breathing ( n = 15), and subjects performing three different cognitive tasks designated as focused attention group (FAG), ( n = 24). HRV is analyzed using coherence plots, spectrograms, HRV parameters, and instantaneous frequency recurrence plots (IFRP). Results: HRV is similar among YG and PBG (at BR <12 cpm) and significantly different for YG vs. NBG ( p < 0.001) and PBG vs. NBG ( p < 0.001). Regularity of breathing oscillations observed in HR is quantified using IFRP and is identical among FAG, PBG, and YG and significantly different for YG vs. NBG ( p < 0.01), PBG vs. NBG ( p < 0.01), and FAG vs. NBG ( p < 0.05). Conclusions: Low‐frequency breathing (BR <12 cpm) plays a primary role in eliciting physiologically significant changes in HRV. By identifying a similarity in breathing oscillations of HR of FAG, YG, and PBG, the results recognize the coexistence of attention and breathing strategies and postulate their joint role in sustaining autonomic benefits, while effects induced by breathing alone on HRV could be attained even intermittently.